Decoding Toxic Romance: A Saussurean Perspective on 'A Little Piece of Heaven' by Avenged Sevenfold - Ajeng Arieska Pramesti (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
This study examines the semiotic construction of obsession in the song "A Little Piece of Heaven" by Avenged Sevenfold. Unlike conventional portrayals of romance, the song presents a complex and provocative narrative of control, emotional disturbance, and posthumous revenge. Using Roland Barthes’ semiotic theory, this research employs a qualitative approach to analyze the denotative and connotative meanings embedded in the lyrics. Each verse is examined as a sign that reflects deeper cultural messages and ideological codes surrounding possessiveness and toxic relationships. The analysis reveals how the song constructs a symbolic discourse on love that transforms into domination, revealing the thin line between affection and obsession. This study argues that such lyrical constructions may influence audience interpretations, especially among adolescent listeners, and highlights the importance of media literacy in understanding metaphorical and violent content in popular music. The findings contribute to the field of communication studies by offering insight into how music lyrics operate as cultural texts and vehicles for ideological meaning.